2021
DOI: 10.1038/s41531-021-00199-2
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease multimodal imaging: F-DOPA PET, neuromelanin-sensitive and quantitative iron-sensitive MRI

Abstract: Parkinson’s disease (PD) is a neurodegenerative synucleinopathy characterized by the degeneration of neuromelanin (NM)-containing dopaminergic neurons and deposition of iron in the substantia nigra (SN). How regional NM loss and iron accumulation within specific areas of SN relate to nigro-striatal dysfunction needs to be clarified. We measured dopaminergic function in pre- and postcommissural putamen by [18F]DOPA PET in 23 Parkinson’s disease patients and 23 healthy control (HC) participants in whom NM conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 87 publications
0
27
0
Order By: Relevance
“…Several mutations in ferroptosis genes have been linked to PD (Table 1), including DJ-1, autosomal recessive PD gene, that encodes a negative modulator of ferroptosis [16]. Moreover, the characteristics of ferroptosis induction are highly consistent with the pathological changes observed in PD patients, including increased iron content [4,5], lipid peroxidation [17][18][19], and defects in the antioxidant system such as decreased levels of cystine/ glutamate antiporter (xCT) [20], glutathione (GSH) [21], DJ-1 (that maintains cysteine and GSH biosynthesis) [16], and CoQ10 [22]. Furthermore, ferroptosis was observed in different PD cellular and animal models such as SH-SY5Y cells treated with MPP + and 6-OHDA, and MPTP-lesioned mice [8][9][10].…”
Section: Evidence Of Ferroptosis In Pd Pathologymentioning
confidence: 85%
See 1 more Smart Citation
“…Several mutations in ferroptosis genes have been linked to PD (Table 1), including DJ-1, autosomal recessive PD gene, that encodes a negative modulator of ferroptosis [16]. Moreover, the characteristics of ferroptosis induction are highly consistent with the pathological changes observed in PD patients, including increased iron content [4,5], lipid peroxidation [17][18][19], and defects in the antioxidant system such as decreased levels of cystine/ glutamate antiporter (xCT) [20], glutathione (GSH) [21], DJ-1 (that maintains cysteine and GSH biosynthesis) [16], and CoQ10 [22]. Furthermore, ferroptosis was observed in different PD cellular and animal models such as SH-SY5Y cells treated with MPP + and 6-OHDA, and MPTP-lesioned mice [8][9][10].…”
Section: Evidence Of Ferroptosis In Pd Pathologymentioning
confidence: 85%
“…Activated glia may act as 'double-edged swords' because they can exert neuroprotective effects by releasing neurotrophic factors and phagocytosis, while mediating neuronal damage by releasing proinflammatory cytokines [3]. Brain imaging and pathological studies have shown correlations between iron deposition in the SNpc of PD patient brains and DA neuronal loss [4,5], indicating that imbalance of iron homeostasis may be a factor closely associated with neuronal death in PD. This type of iron-dependent cell death is termed ferroptosis [6].…”
Section: Glia Activation and Iron Accumulation In The Pathogenesis Of Pdmentioning
confidence: 99%
“…Parkinson Disease ↓ Fe in serum/plasma [107] ↑ Fe in substantia nigra [108,109] ↑ Fe in neurons and adjacent neuropil, microglia, perivascularly in extracellular deposits [110][111][112] Fe bound to neuromelanin in dopaminergic neurons [112,113] Alzheimer Disease ↓ Fe in serum/plasma [114][115][116] ↑ Fe in (mostly temporal) cortex, globus pallidus, caudate, putamen [117][118][119][120][121][122] ↑ Fe in amyloid plaques, microglia, along myelinated fibers [117,[123][124][125] Fe bound to amyloid partially composed of magnetite nanoparticles [126,127] Amyotrophic Lateral Sclerosis ↑ ferritin, ↓ transferrin in serum [128] ↑ Fe in liver, kidneys [129] ↑ Fe in spinal cord [130,131] ↑ Fe in motor cortex, caudate, subthalamic nucleus, globus pallidus, substantia nigra, red nucleus [132][133][134] ↑ Fe in spinal cord neuron nuclei [135] ↑ Fe in microglia in motor cortex [136] n.a.…”
Section: Macroscopic Cellular Subcellularmentioning
confidence: 99%
“…Brain regions affected early in PD include SN, LC, olfactory bulb, and dorsal motor neurons of the vagus nuclei [281,282]. However, iron accumulation in PD is limited to SN pars compacta [108,109].…”
Section: Iron Accumulation and Pathology In Sporadic Neurodegenerativ...mentioning
confidence: 99%
“…Atypical parkinsonian syndromes (APS), such as multiple system atrophy (MSA), progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), and dementia with Lewy bodies (DLB), are other causes of Parkinsonism. Although the clinical progression and pathology can differ between Parkinsonism, there are evident difficulties for achieving confirmed diagnosis based solely on clinical features, particularly in the elderly and in patients at an early stage of disease [ 1 , 2 ]. To date, the therapeutic strategies for these chronic neurodegenerative disorders are based on symptomatic treatments.…”
Section: Introductionmentioning
confidence: 99%